Profeten gevraagd!: Enkele gedachten van prof.dr. C. Graafland over de gave van profetie - Guijt, G. (Theologia reformata, 2025)
This article examines Cornelis Graafland's (1928-2004) views on the gifts of the Spirit, especially that of prophecy, in three parts. First, it examines the reason for Graafland's interest in the spiritual gifts. Second, it appraises Graafland’s dogmatic description of the gifts in general and the gift of prophecy in particular. That is, if prophecy is the proclamation of God's will and word, especially in view of the present situation and the future, then it must be distinguished from preaching on the one hand and political speech on the other. Third, on the basis of Graafland's views, this article explores contemporary claims of prophetic preaching to determine whether they are truly prophetic.